A cyclic scheduling approach to maintaining production flow robustness. (January 2018) - Bocewicz, Grzegorz; Nielsen, Izabela; Banaszak, Zbigniew; Majdzik, Pawel
The organization of flow production, which is typical found in assembly processes, involves a repetitive, fixed-takt time flow of same-size production batches. The cyclic nature of the production flow, which ensures a steady production rhythm, enables just-in-time planning and organization of the associated supply chains. Disruptions in the operation of machinery and equipment, which occur in practice, lead to deviations from nominal operation times. These types of local disturbances lead to changes in production takt time, making it necessary to adjust previously created schedules for delivery/reception of materials and products. Assuming that a control action can be taken to adjust transport operation times within a specified time range, the problem of cyclic scheduling of production flows boils down to seeking conditions the satisfaction of which will guarantee robustness to this kind of disruptions. Satisfaction of robustness conditions allows a return to the nominal production takt time and appropriate adjustment of the production flow trajectory (which makes it possible for the system to return to the previously scheduled delivery times). Numerous examples are included to illustrate the principles of the proposed research methodology aimed at finding solutions for robust scheduling of fixed-takt time production flow.